ANALISIS HUKUM INTERVENSI KEMANUSIAAN ORGANISASI INTERNASIONAL DALAM KONFLIK UKRAINA DAN RUSIA - Gea, Kurniawati; Lombok, Lesza Leonardo; Saroinsong, Sam Julius Richard (Jurnal Yustitia, 2025)
Efforts to prevent or stop human rights violations in a country, either with or without the consent of the country (a country in internal conflict), are known as interventions, with the aim of analyzing the contribution of international organizations in dealing with humanitarian issues during the course of the conflict. Apart from that, this research also evaluates the effectiveness of these interventions in supporting peace efforts and protecting the rights of affected residents. The research method used is a normative research method with a conceptual approach and a comparative approach. This research examines the role of international organizations in humanitarian intervention related to the conflict between Russia and Ukraine. One of the main focuses is the role of the United Nations (UN) in efforts to resolve the conflict and enforce the humanitarian crisis that occurred. The results of this research are that humanitarian intervention by international organizations in the Ukrainian and Russian conflicts is very important in increasing the suffering of the civilian population. Despite facing various challenges such as limited access and pollution for aid, food, medical and protection efforts for seriously injured victims.